2016
DOI: 10.1248/bpb.b16-00250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Steaming Process on Quality of Postharvest <i>Cistanche deserticola</i> for Medicinal Use during Sun Drying

Abstract: Effect of steaming on postharvest stems of Cistanche deserticola Y. C. MA was evaluated periodically during sun drying in both years. Steamed stems exhibited oily black in color, slightly heavier and longer than untreated ones. The levels of five phenylethanoid glycosides and 2,2-diphenyl-1-picrylhydrazyl free radical (DPPH) scavenging activity in steamed stems remained relatively stable during sun drying. Steamed samples showed higher amounts of water-soluble extracts, dilute ethanol-soluble extracts, soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Iridoids possess anti-inflammatory activities [ 15 , 16 ]. It has also been revealed by earlier studies that some chemical components showed variations during the processing [ 17 20 ]. Based on these reports, it can be assumed that post-processing, the variations in chemical composition lead to various pharmacological effects, which need to be further explored.…”
Section: Introductionmentioning
confidence: 86%
“…Iridoids possess anti-inflammatory activities [ 15 , 16 ]. It has also been revealed by earlier studies that some chemical components showed variations during the processing [ 17 20 ]. Based on these reports, it can be assumed that post-processing, the variations in chemical composition lead to various pharmacological effects, which need to be further explored.…”
Section: Introductionmentioning
confidence: 86%
“…(9). Previous studies have shown that steaming can promote the accumulation of active ingredients in Cistanche deserticola, such as phenylethanoid glycosides, soluble sugars, and polysaccharides, accompanied by blackening of appearance color (9)(10)(11). However, most of the previous studies focused on certain specific compounds, very rare research are about the changes in all the chemical compounds and the metabolite conversion mechanism during processing.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the harvested Cistanche deserticola rhizome was steamed in a steaming boiler at 93°C for 30 min and then dried at 60°C until the moisture content of 10% on a wet basis (w.b.) ( 9 ). Previous studies have shown that steaming can promote the accumulation of active ingredients in Cistanche deserticola , such as phenylethanoid glycosides, soluble sugars, and polysaccharides, accompanied by blackening of appearance color ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Iridoids possess anti-inflammatory activities [15][16]. It has also been revealed by earlier studies that some chemical components showed variations during the processing [17][18][19][20]. Based on underlined reports, it has also been considered that post-processing, the variations in chemical composition led to various pharmacological effects, which needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%